Hubungan Pengetahuan Dan Dukungan Keluarga Dengan Perilaku Pencegahan Stunting Pada Ibu Hamil Di Wilayah Kerja Puskesmas Telaga Dewa Kota Bengkulu Tahun 2025 - Monica Sella; Danur Azissah; Emi Pebriani (Jurnal Multidisiplin Dehasen (MUDE), 2026)
In Bengkulu Province, according to the 2024 Indonesian Nutritional Status Survey (SSGI), stunting rates in toddlers reached 18.8%. The highest stunting rate was in Rejang Lebong Regency at 24.7%, followed by Central Bengkulu Regency at 23.4% and Lebong Regency at 22.7%. Bengkulu City ranked ninth with 16.1% of cases. The purpose of this study was to determine the relationship between knowledge and family support and stunting prevention behaviors among pregnant women in the Telaga Dewa Community Health Center (Puskesmas) work area in Bengkulu City in 2025. The research method used was a descriptive cross-sectional approach. Data were collected by distributing questionnaires to 100 pregnant women in the Telaga Dewa Community Health Center work area in Bengkulu City using a simple random sampling technique. Univariate analysis showed that the majority of respondents (65%) had adequate knowledge, the majority (55%) had supportive family support, and the majority (52%) had good stunting prevention behaviors. The results of the bivariate chi-square analysis showed a relationship between knowledge and stunting prevention behavior in pregnant women, with a p-value of 0.000. There was a relationship between family support and stunting prevention behavior in pregnant women, with a p-value of 0.000. The researchers recommend that Community Health Centers (Puskesmas) improve their education programs for pregnant women regarding stunting prevention by involving husbands or close family members.